Age-associated changes in human carotid atherosclerotic plaques. (2nd October 2016) - Pelisek, Jaroslav; Wendorff, Heiko; Wendorff, Carina; Kuehnl, Andreas; Eckstein, Hans-Henning
Abstract: Little is known about changes in carotid plaque morphology during aging and the possible impact on cardiovascular events. Only few studies addressed so far age-related modifications within atherosclerotic lesions. Therefore, in this work we endeavored to summarize the current knowledge about changing of plaque composition in elderly. The data from hitherto existing studies confirm that atherosclerotic plaques undergo distinct alternations with advanced age. However, the results are often ambiguous and the changes do not seem to be as disastrous as expected. Interestingly, none of the studies could definitely evidence increased plaque vulnerability with advanced age. Nevertheless, based on the previous work showing decrease in elastin fibers, fibroatheroma, SMCs, overall cellularity and increase in the area of lipid core, hemorrhage, and calcification, the plaque morphology appears to transform toward unstable plaques. Otherwise, even if inflammatory cells often accumulate in plaques of younger patients, their amount is reduced in the older age and so far no clear association has been observed between thin fibrous cap and aging. Thus, the accurate contribution of age-related changes in plaque morphology to cardiovascular events has yet to be elucidated. KEY MESSAGES: Composition of carotid atherosclerotic lesions changes during aging. These alternations are however, just moderate and depend upon additional variables, such as life style, accompanying disease, genetics, and other factors that have yet to be determined. Based on the current data, the age-associated plaque morphology seems to transform toward vulnerable plaques. However, the changes do not seem to be as disastrous as expected.